2020
DOI: 10.1007/s13201-020-1173-8
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of water quality in river Molo water basin, Kenya

Abstract: The monitoring of water quality for both domestic and commercial use is absolutely essential for policy formulation that affects both public and environmental health. This study investigates the quality of water of river Molo system which lies in the Kenyan Rift Valley. The river is considered a vital source of water for the residents and industrial activities in Nakuru and Baringo Counties. Six water samples were collected during the dry season of December 2017. Various physicochemical parameters were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 36 publications
(63 reference statements)
1
19
0
Order By: Relevance
“…Despite the study area being characterized by a multiple of anthropogenic activities that could be linked to sources of surface water pollution with different chemical and viral contaminants, no relevant research has been reported on the same. Achieng et al ( 32 ) and Chebet et al ( 33 ) reported on the concentration of some of these chemical contaminants from some water sources in Kenya. However, these studies were focused about chemical pollution only and did not attempt to link the results with enteric virus contamination of the source waters.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the study area being characterized by a multiple of anthropogenic activities that could be linked to sources of surface water pollution with different chemical and viral contaminants, no relevant research has been reported on the same. Achieng et al ( 32 ) and Chebet et al ( 33 ) reported on the concentration of some of these chemical contaminants from some water sources in Kenya. However, these studies were focused about chemical pollution only and did not attempt to link the results with enteric virus contamination of the source waters.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the average concentration of Na + was 8751.80214.04 mgL -1 which is approximately 44 times above the permissible limit of 200 mgL -1 [18]. The high Na + levels may result from sewage discharge, domestic effluents, leachates of Na + containing rocks and recharge water from underground systems which are rich in brine [42]. With absence of desalination plants to extract the brine in the water, these regions experiences low Agricultural productivity.…”
Section: Discussionmentioning
confidence: 78%
“…The EC depends on concentration, mobility, valence, type of ions present and temperature [42,49]. As a parameter used to assess water purity, it indicates the amount of total dissolved ions [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the water quality analysis, water samples were collected at the sources and outlet points of the sub-watersheds and at the main outlet of the Kebena river watershed. A total of eight sampling sites (each for the dry and wet seasons) were selected to collect the water samples from the river (Chebet et al 2020;Goshu 2007;Sliva and Williams 2001). The seasonal samples were collected for two consecutive years in 2016 and 2017.…”
Section: Water Quality Analysismentioning
confidence: 99%